2016
DOI: 10.1002/anie.201606722
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of a Fluorinase for Improved Fluorination Efficiency with a Non‐native Substrate

Abstract: Fluorinases offer an environmentally friendly alternative for selective fluorination under mild conditions. However, their diversity is limited in nature and they have yet to be engineered through directed evolution. Herein, we report the directed evolution of the fluorinase FlA1 for improved conversion of the non-native substrate 5'-chloro-5'-deoxyadenosine (5'-ClDA) into 5'-fluoro-5'-deoxyadenosine (5'-FDA). The evolved variants, fah2081 (A279Y) and fah2114 (F213Y, A279L), were successfully applied in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 42 publications
0
35
0
2
Order By: Relevance
“…439 Directed evolution of halogenases too is expanding the substrate scope of halogenating enzymes, pushing them as viable complementary catalysts in complex synthetic schemes. 440442 …”
Section: Future Perspectivesmentioning
confidence: 99%
“…439 Directed evolution of halogenases too is expanding the substrate scope of halogenating enzymes, pushing them as viable complementary catalysts in complex synthetic schemes. 440442 …”
Section: Future Perspectivesmentioning
confidence: 99%
“…[14] A direct evolution of fluorinase for improved fluorination efficiency was also recently reported. [15] For instance, arginylglycylaspartic acid (RDG) peptide 14 bound to 5′-chloro-5′-deoxy-2-ethynyladenosine (ClDEA) through a tetraethylene glycol (TEG) linker could be labeled with fluorine-18 for late-stage modification (Figure 3). Specifically, an aqueous solution of [18 F]fluoride, directly from the cyclotron target, was reacted with RDG-TEG-CIDEA in the presence of L-SeMet at room temperature for 30 min to afford the radiolabeled product 15 in 12% RCY (non-decay corrected).…”
Section: Direct Methods For 18f-labeling Of Biomoleculesmentioning
confidence: 99%
“…[13][14][15][16] There are only a handful of reports demonstrating limited success at enhancing substrate specificity through enyzme modification. 4,6,10,13,18 The challenge here is the lack of understanding of the fluorinasesubstrate interactions to enable a better engineered enzyme for fluorination.…”
mentioning
confidence: 99%
“…15,16,[19][20][21][22][23][24] We have recently demonstrated that the catalytic efficiency of FlA1 fluorinase on a non-native substrate 5 0 -ClDA can be improved via directed evolution. 18 With the improved variants as a starting point, we probed their promiscuity against substrates that are modified at the C-2 (R 1 substitution) and the unexplored C-6 (R 2 substitution) positions of the adenine ring (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation